A Quantitative Trade Model with Unemployment - Kyu Yub Lee (East Asian Economic Review (EAER), 2019)
I employ search-and-matching to a multi-country and multi-sector Ricardian model with input-output linkages, trade in intermediate goods, and sectoral heterogeneity, in order to quantify the welfare effects from tariff changes. The paper shows that labor market frictions can be a source of comparative advantage in the sense that better labor market conditions contribute to lower cost in production. Labor market frictions play a critical role in determining the probability of exporting goods to trading partners, and interact with bilateral trade share, price, expenditures, etc. Unemployment and changes in unemployment rates due to tariff reductions contribute welfare changes across countries, implying that welfare effects based on quantitative trade models with full-employment are likely to be biased. I confirm the biased welfare effects by revisiting Caliendo and Parro (2015), who conduct an analysis of the welfare effects from the NAFTA from 1993 to 2005. I show that the welfare gap between theirs and mine has a positive correlation with changes in observed unemployment rates across countries. With the constructed model, I further conduct counterfactual exercises by asking what would happen if China's tariffs remain unchanged from 2006 to 2015. It turns out that there are mild welfare effects to trading partners in the world trading system.
Keywords: F10; F17; F60; 330; Quantitative Trade Model; Unemployment; Labor Market Frictions; Welfare; Tariff Reductions